RAD51 separation of function mutation disables replication fork maintenance but preserves DSB repair - Son, Mi Young; Belan, Ondrej; Spirek, Mario; Cibulka, Jakub; Nikulenkov, Fedor; Kim, You Young; Hwang, Sunyoung; Myung, Kyungjae; Montagna, Cristina; Kim, Tae Moon; Krejci, Lumir; Hasty, Paul (iScience, 2024)
Homologous recombination (HR) protects replication forks (RFs) and repairs DNA double-strand breaks (DSBs). Within HR, BRCA2 regulates RAD51 via two interaction regions: the BRC repeats to form filaments on single-stranded DNA and exon 27 (Ex27) to stabilize the filament. Here, we identified a RAD51 S181P mutant that selectively disrupted the RAD51-Ex27 association while maintaining interaction with BRC repeat and proficiently forming filaments capable of DNA binding and strand invasion. Interestingly, RAD51 S181P was defective for RF protection/restart but proficient for DSB repair. Our data suggest that Ex27-mediated stabilization of RAD51 filaments is required for the protection of RFs, while it seems dispensable for the repair of DSBs.
Keywords: Molecular biology; Genetics; Properties of biomolecules; Molecular interaction